IRS-2 G1057D polymorphism in Turkish patients with colorectal cancer - Yukseloglu, Emel Hulya; Celik, Sevim Karakas; Kucuk, Meral Urhan; Yalin, Erdinc; Ozkal, S. Sebnem; Ates, Cengiz; Berkoz, Mehmet; Yalin, Serap; Ates, Nurcan Aras (Gastroenterology Review/Przegląd Gastroenterologiczny, 2014)
Introduction : Gene polymorphisms have a broad range of analysis, but are of particular use in molecular medicine due to their potential in revealing the genetic tendency in diseases such as cancer, heart attack etc. These studies basically depend on mutations that can be detected by proper techniques. The genes coding the insulin receptor substrate (IRS) proteins are among the most widely analysed polymorphisms in various cancer types, in which a G1057D mutation is seen. Aim: To determine the risk of colon cancer by analysing the IRS-2 gene polymorphism in Turkish patients. Material and methods: A total of 161 newly diagnosed colorectal cancer patients were analysed and compared to 197 unrelated healthy controls. A polymerase chain reaction-based restriction fragment length polymorphism method was carried out. Results: No differences were observed between the patient and control groups for both allele and genotype frequencies of the IRS-2 G1057D gene. Conclusions: Our results demonstrated that IRS-2 G1057D polymorphism is not associated with colorectal cancer in the Turkish population. This research is a preliminary and original study in Turkish patients with colorectal cancer. It also provides population-level genetic data on IRS-2 in the Turkish population. Further studies should be performed on larger number of patients and controls for more reliable results about the genetic tendency in colorectal cancer in Turkey. The study is a collaborative work of different universities and scientists.